Psikospiritual Islam dan Perilaku Terorisme di Indonesia: Upaya Memahami Motif Perilaku Kekerasan Berdalih Jihad di Indonesia - Santoso, Agus; Kurnia Sari, Dita; Abdullah, Abdullah (Journal of Sufism and Psychotherapy, 2023)
The application of Islamic psychospiritual counseling can use various therapeutic techniques such as meditation, self-healing, trauma healing, and so on. As a form of providing solutions to improve mental health and develop aspects of an individual's spirituality and religiosity to become a different individual than before. Handling violent behavior under the pretext of jihad through healing techniques to form a constructive self both in terms of cognition, feelings and behavior and focusing on aspects of the belief system. to further examine terrorism from a psychospiritual (psychological and religious) perspective in relation to models of acts of terrorism or violence in Indonesia. This research is a descriptive qualitative research that tries to describe what and the lessons behind terrorism incidents. The results of this research are: 1). The application of Islamic psychospiritual counseling can use various therapeutic techniques such as meditation, self-healing, trauma healing and so on. As a form of providing solutions to improve mental health and develop aspects of an individual's spirituality and religiosity to become a different individual than before: 2). Handling violent behavior under the pretext of jihad can be done through independent healing techniques with the aim of forming a constructive self both in terms of cognition, feelings and behavior and focusing on aspects of the belief system. The changes experienced by Ali Fauzi practically psychologically can be seen from his current positive self-image by returning and supporting the Republic of Indonesia.